1999
DOI: 10.1046/j.1365-2672.1999.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a bacteriocin produced by Lactobacillus acidophilus IBB 801

Abstract: M. ZAMFIR, R. CALLEWAERT, P.C. CORNEA, L. SAVU, I. VATAFU and L. DE VUYST.1999.Lactobacillus acidophilus IBB 801 produces a small bacteriocin, designated acidophilin 801, with an estimated molecular mass of less than 6·5 kDa. It displays a narrow inhibitory spectrum (only related lactobacilli but including the Gram‐negative pathogenic bacteria Escherichia coli Row and Salmonella panama 1467) with a bactericidal activity. The antimicrobial activity of cell‐free culture supernatant fluid was insensitive to catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 52 publications
6
48
0
Order By: Relevance
“…Production of these factors does not require bacterial-intestinal cell contact. Previously studies have reported that some Lactobacillus strains produce proteinaceous (23) or protease-insensitive (22) anti-bacterial compounds. However, we are unaware of reports indicating that bacterially produced factors regulate either Akt signal transduction or cell survival pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of these factors does not require bacterial-intestinal cell contact. Previously studies have reported that some Lactobacillus strains produce proteinaceous (23) or protease-insensitive (22) anti-bacterial compounds. However, we are unaware of reports indicating that bacterially produced factors regulate either Akt signal transduction or cell survival pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Putative mechanisms of the action of probiotics include regulation of cytokine production (18), such as stimulation of mononuclear cells to generate both pro-and anti-inflammatory cytokines (19,20), enhancement of secretory IgA secretion (21), production of antibacterial substances (22,23), an increase in the integrity of the intestinal barrier (24), and competition with pathogenic microorganisms for enterocyte binding (25). Yet almost nothing is known regarding the basic molecular mechanisms of probiotic regulation of intestinal epithelial health.…”
mentioning
confidence: 99%
“…The generally held view is that bacteriocins exhibit less potential as chemotherapeutics for infections with Gram-negative pathogens. However, it should be noted that several bacteriocins and bacteriocin-like molecules produced by probiotic Lactobacillus strains have been also found to be active against the growth of several Gram-negative gastric or enterovirulent bacterial pathogens, including H. pylori, EHEC, Shigella, Salmonella, and Campylobacter (112)(113)(114)(115)(116).…”
Section: Direct Activities Against Enterovirulent Bacteriamentioning
confidence: 99%
“…Whereas, it was further observed that the differences in the degree of inhibition with various antibiotics were possibly due to their different mode of action on the cell components such as the cell wall, protein and DNA synthesis, DNA gyrase and RNA polymerase (Neu, 1992). Nowadays antibiotic resistance has findings of Zamfir et al (1999) who were of the view that L. acidophilus IBB 801 showed inhibitory spectrum against E. coli and Salmonella panama. Similarly, Jacobsen et al (1999) have reported that 20 out of 47 strains of Lactobacillus spp.…”
Section: Probiotic Characteristics Of Lactobacillus Spp Isolated Fromentioning
confidence: 99%